Protein energy intake, mid-upper arm circumferences and hand-grip strength among hemodialysis patients in Hospital Pakar Universiti Sains Malaysia (HPUSM) - Mior, Sharifah Amirah Awatif Syed (Universiti Sains Malaysia, 2025)
In this study, protein energy intake and mid-upper arm circumferences (MUAC) are known as independent variable while hand-grip strength (HGS) is known as dependant variables. This study investigates the relationship between protein energy intake, mid-upper arm circumferences (MUAC) and hand-grip strength (HGS) among haemodialysis patients at Hospital Pakar Universiti Sains Malaysia (HPUSM). A cross-sectional study was conducted among 80 patients aged 18 years old and above. Data were collected using anthropometry measurement which is mid-upper arm circumferences (MUAC), hand-grip strength (HGS), and dietary intake (3 days 24-hours diet recall). Out of 80 subjects from hemodialysis patients (35 male and 45 female) , it was discovered that there is a positive correlation between mid-upper arm circumferences (MUAC) and hand-grip strength (HGS) among hemodialysis patients with the values (p = 0.004, r = 0.316). There is significantly association between gender and living arrangement (p = 0.044), between gender and monthly household income (p = 0.034), between gender and heart disease (p = 0.002) with men had higher prevalence of heart disease than women, between gender and gout (p = 0.001) with men had higher prevalence of gout than women, between gender and breathing difficulties (p = 0.021) with men has higher prevalence of having breathing difficulties. There is significant association between gender and protein energy intake, mid-upper arm circumferences (MUAC) and hand-grip strength (HGS) with the values (p = 0.023, p = 0.001, p < 0.001). However, there is no statistically significant correlation was found between protein energy intake and hand-grip strength (HGS). Nonetheless, it is suggested to separate between outpatients and inpatients setting in the study because their diet 24-hours diet recall might be different. It will helps to provide clear understanding on the factors affecting hand-grip strength (HGS) to improve muscle mass and muscle strength among haemodialysis patients. Future research should focus on longitudinal studies to establish causal relationships and explore interventions to optimize dietary intake and muscle mass and muscle strength in haemodialysis patients